2012
DOI: 10.1097/shk.0b013e31824989d7
|View full text |Cite
|
Sign up to set email alerts
|

Increased Poly(ADP-Ribosyl)ation in Peripheral Leukocytes and the Reperfused Myocardium Tissue of Rats With Ischemia/Reperfusion Injury

Abstract: The overactivation of the nuclear enzyme poly(ADP-ribose) polymerase (PARP) is considered a final common effector in ischemia/reperfusion (I/R) injury. The aim of the current study was to examine the precise time course of the activation of PARP in peripheral leukocytes and the reperfused myocardium tissue on myocardial I/R injury from the same rat and to identify the relationship between myocardial infarct size and the degree of PARP activation in circulating leukocytes. Another aim of the study was to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In accordance with this model, PARP inhibitors have been shown to protect the myocardium and the brain even when administered up to 4 hours after reperfusion when infarct size was assessed at 24 hours . Our data therefore explain how PARP inhibition provides protection downstream of mPTP opening by revealing that mPTP‐mediated depolarization is not terminal in a significant fraction of the cells in the area at risk.…”
Section: Discussionsupporting
confidence: 75%
“…In accordance with this model, PARP inhibitors have been shown to protect the myocardium and the brain even when administered up to 4 hours after reperfusion when infarct size was assessed at 24 hours . Our data therefore explain how PARP inhibition provides protection downstream of mPTP opening by revealing that mPTP‐mediated depolarization is not terminal in a significant fraction of the cells in the area at risk.…”
Section: Discussionsupporting
confidence: 75%
“…3-AB significantly improved the outcome of myocardial dysfunction, as evidenced by a reduction in creatine phosphokinase levels, diminished infarct size, and preserved the ATP pools (Zingarelli et al, 1997). These findings were subsequently confirmed and extended into various other models using PARP inhibitors of increasing selectivity and potency (Thiemermann et al, 1997; Bowes et al, 1998a; Bowes et al, 1998b; Docherty et al, 1999; Liaudet et al, 2001a, Liaudet et al, 2001b, Faro et al, 2002; Zingarelli et al, 2003; Khan et al, 2003; Kaplan et al, 2005; Song et al, 2008; Eltze et al, 2008; Roesner et al, 2010; Zhang et al, 2012). Furthermore, Zingarelli also demonstrated that PARP deficient mice are protected against myocardial reperfusion injury (Zingarelli et al, 1998; Yang et al, 2000).…”
Section: Beyond Anticancer Therapy: Stroke Circulatory Shock Carmentioning
confidence: 70%
“…area at risk). Most of the poly(ADP-ribose) staining occurs in cardiac myocytes and endothelial cells, indicating that the heart tissue and the vasculature themselves are the main sites of PARP activation (Liaudet et al, 2001a; Liaudet et al, 2001b; Zhang et al, 2012). In addition, PARP activation also occurs in circulating mononuclear cells (Murthy et al, 2004; Toth-Zsamboki et al, 2006).…”
Section: Beyond Anticancer Therapy: Stroke Circulatory Shock Carmentioning
confidence: 99%
“…Following I/R, increased oxidative and nitrosative stress activates the nuclear enzyme poly(ADP-ribose) polymerase (PARP), which catalyzes the cleavage of NAD + into nicotinamide and ADP-ribose [228]. NAD + depletion can interfere with glycolysis, the Krebs cycle, mitochondrial electron transport and lead eventually to ATP depletion.…”
Section: Emerging Concepts Of Redox Therapy In Ischemia/reperfusion Injury and Heart Failurementioning
confidence: 99%